Epistolary Liveness: Narrative Presence and the Victorian Actress in Letters. Issue 2 (10th April 2019) - Eriks Cline, Lauren
Abstract : In an influential essay on the place of autobiography in theatre history, Thomas Postlewait puts Fanny Kemble's memoirs at the crux of a historiographical problem. The literary sensibility of Kemble's work appears to Postlewait an instance of both the theatrical memoir's cultural richness and its limitations as biographical evidence: although Kemble's "epistolary mode of self-representation" gives her autobiography Records of a Girlhood "a documentary quality, " for example, even her "earliest letters reveal a calculated literary style" that signals her awareness of the "traits and conventions" of eighteenth- and nineteenth-century novels. In her consciousness of narrative trends, Kemble stands out as a particularly clear example of a general tendency in theatrical autobiographies of the period. As the nineteenth century's booming print market expanded the audience for stories about theatregoing, it also drew readers who were increasingly familiar with novelistic experiments in plotting, characterization, and point of view. This shared audience encouraged an exchange of discursive conventions across fictional and historical narratives, which makes memoirs a compelling but complicated source of historical data about nineteenth-century theatre. Indeed, the two-way influence between genres is so strong that Postlewait argues scholars "need to ask to what extent these autobiographies exist not only as historical records but as epistolary fictions."